Combination Of HCD, Persona, MVP, and Thumb Zone for Designing TNI Physical Fitness Monitoring Application - Wirpan Atmaja Putra; Wahyu Teja Kusuma (Journal of Enhanced Studies in Informatics and Computer Applications, 2024)
This research contributed to producing a combination of design methods and design of the Indonesian National Army (TNI) physical fitness monitoring application. This research is very important because TNI institutions really need a physical fitness monitoring application to be able to make the right decisions. The design of the physical fitness monitoring application primarily uses the Human-Centered Design (HCD) method which is then combined with the Persona, Minimum Viable Product (MVP) and The Thumb Zone methods. The combination of HCD with Persona has been proven to be used to understand and determine usage content and user needs. The combination of HCD with MVP has proven to be able to be used to produce design solutions to meet user needs. The combination of HCD with Thumb Zone has proven to be able to be used to evaluate designs against user needs. Finally, as many as 20 Persona respondents agreed that the combination of HCD, Persona, MVP, and Thumb Zone proved reliable for producing physical fitness monitoring application design solutions that can be used naturally and meet the needs of TNI.